(untitled) (Journal of Medicine, 2009)
1068 randomly sampled adult Bangladeshi people were studied during a period of six months from October 2004 to March 2005. It was a randomized, prospective study. Cases that fulfilled two criteria of metabolic syndrome (MetS) were evaluated to see pattern and types of MetS. Out of 1068 patients, 110 (10.3%) fulfilled the inclusion criteria. 101 (9.4%) cases were labeled as metabolic syndrome according to NCEP ATP III criteria, 09 cases had only two criteria. 40 cases were male & 70 cases were female (M:F= 1:1.8). Mean age of patients with was 44.88, ranging from the age of 20-68 years. Majority (55%) of the patients were in the age group of 30-49 years. Half of the cases had BMI 30-34.9. Mean body weight of male was 85.9 kg and of female was 78.2 kg. Mean waist circumference of male was 41.7 inches and of female 40 inches. Mean HDL for male was 38.3 mg/dL and for female is 40.2 mg/dL. Mean Triglyceride for male was 172.1 and for female was 169.3 mg/dL. Mean total cholesterol for male was 216.7 and for female was 207.6 mg/dL. Mean systolic blood pressure (SBP) for men is 162 mm Hg & diastolic blood pressure (DBP) 99 mm Hg and for female mean SBP 155 and DBP 96 mm Hg. Metabolic syndrome is more prevalent in the 3rd and 4th decade of life in both sexes. It is almost twice common in female than male. Combination of hypertension, obesity & dyslipidemia comprises nearly 40% of its presentation. doi: 10.3329/jom.v10i2.2813 J MEDICINE 2009; 10 : 48-51